An update of electro surgery devices options in minimal invasive surgery: a review - Raj, Aman Deep; Chhavi R. Baid; Syeda Afreen Fatima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
The rate and variety of advances in energy sealing technology in the last two decades has heralded new opportunities in laparoscopic and minimally invasive surgery. Reduced operating times, lower postoperative pain scores, and shorter length of stay are offset by the additional cost of such instruments. Critical to obtaining optimal clinical effects and reducing potential complications, is a thorough understanding of the proper use of each energy modality. No single device has shown a significant superiority over the other. However best combination to have is harmonic along with ligasure or perhaps now the latest wireless sonicision with ligasure to undertake most of the surgeries. Thunderbeat has advantages like faster cutting speed and minimal instrument changes. Ferromagnetic wand is the fastest available instrument with unique features. Argon beam coagulation has certain specific uses and is best for fulguration and it is definitely advantageous to have it in OT. Sonicision offered wireless ergonomics and better manoeuvrability, cheapest VSD was the conventional bipolar.